ADVANTAGES AND DISADVANTAGES OF WTO MEMBERSHIP FOR UZBEKISTAN - Donishev, Sardor (Архив научных исследований, 2022)
The article presents ideas and studies on the impact of WTO membership on international trade relations, the economic consequences of joining the WTO, the policy of the Republic of Uzbekistan to achieve WTO membership, as well as the state of this process and efforts aimed at membership in the preconditions before independence and after independence, the path to membership in the WTO, the development of the World Trade Organization, as well as how effective or dangerous this merger is for developing countries, including Uzbekistan.